ANALISIS KOMPARATIF KURIKULUM CINTA DAN KURIKULUM MERDEKA DALAM PERSPEKTIF PENGEMBANGAN KARAKTER PESERTA DIDIK - Nurhuda; Rama Trian Caetheby; Lusi Suswanti; Septiana Indriani Br Gultom; Mujiburrahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to comparatively analyze the Love Curriculum (Kurikulum Cinta) and the Merdeka Curriculum from the perspective of students' character development. The research employed a qualitative approach using a library research design. Data were collected from policy documents, academic books, scholarly journal articles, and other relevant literature related to the Love Curriculum, the Merdeka Curriculum, and character education. Data analysis was conducted through data reduction, data display, comparative analysis, and conclusion drawing. The findings indicate that the Merdeka Curriculum emphasizes competency development through differentiated instruction, project-based learning, and the strengthening of the Pancasila Student Profile. In contrast, the Love Curriculum focuses on internalizing the values of compassion, religious moderation, respect for human dignity, and the establishment of a humanistic school culture. Although the two curricula differ in their philosophical foundations, curriculum structure, learning approaches, and assessment systems, they share the same objective of developing students who are competent, morally grounded, and capable of living harmoniously in a diverse society. This study proposes an Integrated Character Development Model Based on Competence and Compassion as a conceptual synthesis that combines the strengths of both curricula. The proposed model is expected to contribute to strengthening the implementation of character education in Indonesia.